An e-readiness assessment tool for local authorities: a pilot application to Iraq - Musa, Mohammed Raji (AUC Knowledge Fountain, 2010)
Measuring e-readiness is vital to embrace e-government successfully. Sophistication of available tools and lack of capacity at municipal level makes it important to consider e-readiness assessment tools for municipalities. This study proposes a tool for measuring e-readiness in municipalities and it was conducted in two Iraqi governorates. Data was collected, for this studay, quantitatively and qualitatively relying on questionnaires for public internet users and government employees, and IDIs. Several aspects were investigated and then used in the tool that was designed to qualify for the use of local officials in Iraq as a pilot case for developing countries. Indicators were categorized into three groups, infrastructure, human resources, and government and management. Measuring e-readiness in municipalities is a trade off between simplicity with acceptable level of information and sophistication with accurate information. The proposed tool relies on collecting data easy to find and access to meet the condition of simple and reliable use by officials in local governments. This is expected to help these officials to identify issues to focus in development of community aspects to raise e-readiness and reap the benefits of e-government.